The design of artificial enzymes, novel chiral organocatalysts and new ligation technologies - Tallon, Seán (Trinity College (Dublin, Ireland). School of Chemistry, 2013)
An investigation into the mode of action of aldehyde dehydrogenase enzymes was undertaken through the synthesis of a series of compounds that were hypothesised as potential biomimetics. This study revealed the possible role of a basic moiety in the mode of action of the enzyme, however it also demonstrated the incompatibility of thiol and pyridinium ion-based moieties incorporated in the same structure. The ineffectiveness of the biomimetics was a testament to the evolutionary design of the enzymes themselves.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin.